Discovery of Homobivalent Bitopic Ligands of the Cannabinoid CB2 Receptor. Issue 68 (9th November 2020) - Morales, Paula; Navarro, Gemma; Gómez‐Autet, Marc; Redondo, Laura; Fernández‐Ruiz, Javier; Pérez‐Benito, Laura; Cordomí, Arnau; Pardo, Leonardo; Franco, Rafael; Jagerovic, Nadine
Abstract: Single chemical entities with potential to simultaneously interact with two binding sites are emerging strategies in medicinal chemistry. We have designed, synthesized and functionally characterized the first bitopic ligands for the CB2 receptor. These compounds selectively target CB2 versus CB1 receptors. Their binding mode was studied by molecular dynamic simulations and site‐directed mutagenesis. Abstract : Single chemical entities with potential to simultaneously interact with two binding sites are emerging strategies in GPCR pharmacology. We present herein the design, synthesis and functional characterization of the first bitopic ligands for the CB2 receptor. Molecular understanding of the binding mode was guided by molecular dynamic simulations and site‐directed mutagenesis.